High ambulatory blood pressure in male professional football players - Berge, H. M.; Andersen, T. E.; Solberg, E. E.; Steine, K. (British Journal of Sports Medicine, 2013)
Background No data exist on ambulatory blood pressure (ABP) in athletes. Objectives To identify ABP and examine recommended follow-up of high office blood pressure (OBP) in male professional football players and secondary study indicators of sympathetic activity. Methods Players with high OBP (cases) from a previous screening of 594 players (n=28) were matched for age and ethnicity with players with optimal OBP (controls). High ABP was defined as a mean of =135/85 mm Hg during daytime and =120/75 mm Hg during night-time. The players replied to questions regarding follow-up of high OBP. High night-time ABP and lack of nocturnal dip (=10% decline in average BP) were taken as indicators of increased sympathetic activity. Results 26 cases and 26 controls, mean age 28±4 years, were included. 15 (58%) of the cases had sustained hypertension and 11 (42%) white coat hypertension. Among the controls, 17 (65%) had normotension and 9 (35%) masked hypertension. ABP during night-time was high in 23 (88%) of the cases and in 16 (64%) of the controls, and nocturnal dip was absent in 9 (35%) and 11 (42%), respectively. 10 (38%) of the cases had no follow-up of high OBP. Conclusions More than one-third of the players with optimal OBP had masked hypertension during daytime and more than half of all players had high ABP during night-time, which are novel findings in athletes. Together with the reduced nocturnal dip, this might indicate increased sympathetic activity. Follow-up of high OBP after preparticipation screening is random and should be organised.